Antibiotic resistance genes, class 1 integrons, and IncP-1/IncQ-1 plasmids in irrigation return flows. (February 2020) - Dungan, Robert S.; Bjorneberg, David L.
Abstract: Surface waters could be a dominant route by which antibiotic resistance genes (ARGs) are disseminated. In the present study we explored the prevalence and abundance of ARGs [ bla CTX-M-1, erm (B), sul1, tet (B), tet (M), and tet (X)], class 1 integron-integrase gene ( intI1 ), and IncP-1 and IncQ-1 plasmids in eight irrigation return flows (IRFs) and a background site (Main Line Canal, MLC) in the Upper Snake Rock watershed in southern Idaho. Grab samples were collected on a monthly basis for a calendar year, which were processed to extract microbial DNA, followed by droplet digital PCR to quantify the gene copies on an absolute (per 100 mL) and relative (per 16S rRNA gene copies) basis. The antibiotic resistance and intI1 genes and IncP-1/IncQ-1 plasmids were recovered at all IRF sampling sites with detections ranging from 55 to 81 out of 81 water sampling events. The bla CTX-M-1 gene was detected the least frequently (68%), while the other genes were detected more frequently (88–100%). All of the genes were also detected at MLC from April to Oct when water was present in the canal. The genes from lowest to greatest relative abundance in the IRFs were: bla CTX-M-1  <  erm (B) <  tet (B) < IncQ-1 <  tet (M) <  sul1  <  intI1  = IncP-1 <  tet (X). When compared to the average annual relative gene abundances in MLC water samples, they were found to be at statistically greater levels ( P  ≤ 0.008) except that of the IncP-1 and IncQ-1 plasmids ( P  = 0.8 and 0.08, respectively). The fact that most IRFs contained higher levels than found in the canal water, indicates that IRFs can be a point source of ARGs that ultimately discharge into surface waters. Graphical abstract: Image 1 Highlights: An investigation of antibiotic resistance genes (ARGs) was conducted in an Idaho watershed. Irrigation return waters contained higher ARG levels than at a background canal site. Irrigation return flows can be a point source of ARGs and enhance their environmental dissemination.